Second Generation Patents in Pharmaceutical Innovation - Ahn, Hyewon (Munich Intellectual Property Law Center - MIPLC, 2014)
The development of new medications and improvements thereof are crucial to ensure continued gains in health. The development process is long and costly, and mainly to produce the information to meet high regulatory requirements. In contrast, imitation involves negligible costs and much reduced risks. This is one of the reasons the pharmaceutical industry depends greatly on patent protection. Despite the existing patent system, however, the number of new medications per year has decreased, especially during the last decade. In comparison, the number of second generation patents and products has been drastically increased. This industry is accused both of neglecting its real mission of providing new medications while generating second generation products, and of preventing the entry of generics. The dissertation reviewed whether the concerns are justified, and, if so, whether or how the patent system can improve the situation that confronts pharmaceutical companies and society.